2006
DOI: 10.1007/s11746-006-5043-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of residual oil from palm‐pressed mesocarp fiber (Elaeis guineensis) using supercritical CO2 with and without ethanol

Abstract: The qualities of oils extracted from fresh and dried palm-pressed mesocarp fiber were evaluated. The means of extraction included conventional solvent extraction and supercritical carbon dioxide (SC-CO 2 ) extraction with and without addition of ethanol. Extraction efficiency using pure SC-CO 2 and the effect of moisture content on efficiency were studied. Minor components, such as vitamin E, carotenoids, squalene and phytosterols, obtained by different methods were compared. The quality of oil recovered from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 13 publications
1
41
0
3
Order By: Relevance
“…This residual oil can be recovered by conventional solvent extraction using n-hexane, but PPF oil extracted by supercritical carbon dioxide (SC-CO 2 ) was reported to be cleaner and clearer [67]. Analysis of the extracted oil quality also showed that the incorporation of ethanol in the SC-CO 2 extraction produced oil with higher oxidative stability compared to extraction using SC-CO 2 alone.…”
Section: Recovery Of Functional Component-enriched Oil From Ppfmentioning
confidence: 99%
“…This residual oil can be recovered by conventional solvent extraction using n-hexane, but PPF oil extracted by supercritical carbon dioxide (SC-CO 2 ) was reported to be cleaner and clearer [67]. Analysis of the extracted oil quality also showed that the incorporation of ethanol in the SC-CO 2 extraction produced oil with higher oxidative stability compared to extraction using SC-CO 2 alone.…”
Section: Recovery Of Functional Component-enriched Oil From Ppfmentioning
confidence: 99%
“…Impregnation of active compounds into polymers is a developing area under SFC. It has been successfully used for extraction and purification of vitamin E from palm oil (Lau et al 2006). Solvent residues in pharmaceutical and food products are being prohibited by the regulatory agencies since 1970s.…”
Section: Industrial Applications Of Scfs and Sfcsmentioning
confidence: 99%
“…A laboratory-scale supercritical fluid extraction system which has been described previously (Lau et al, 2006) was used for this study. The CO 2 was chilled and delivered to the system by a high-pressure diaphragm pump (PU-986, Jasco, Japan).…”
Section: Sc-co 2 Extraction Systemmentioning
confidence: 99%
“…It is known that palm-pressed fiber oil is enriched with natural carotene, vitamin E, sterols, squalene, co-enzyme Q 10 , and phenolic compounds (Choo et al, 1996;Lau, Choo, Ma, & Chuah, 2005a;Lau, Choo, Ma, & Chuah, 2006). These functional components have been determined to possess certain biological activities such as b-carotene having antioxidant activity and inhibiting growth of colon cancer cells (Di Mascio, Murphy, & Sies, 1991;Slattery et al, 2000); lycopene is particularly an effective singlet oxygen quencher (Di Mascio, Kaiser, & Sies, 1989); vitamin E (e.g., tocotrienols) as antioxidant, anti-cancer and having hypercholesterolemic effects (Pearce, Parker, Deason, Qureshi, & Wright, 1992;Salonen, Salonen, & Penttila, 1985;Tomeo, Geller, Watkins, Gapor, & Bierenbaun, 1995); b-sitosterol possesses cholesterol lowering effect (Hendriks, Westrate, van Vliet, & Meijer, 1999;Moghadasian & Frohlich, 1999); squalene as chemopreventive agent against some type of cancers (Rao, Newmark, & Reddy, 1998;Smith, Yang, Seril, Liao, & Kim, 1998), co-enzyme Q 10 with protective effect against artherosclerosis and heart disease (Kontush, Hubner, Finckh, Kohlschutter, & Beisiegel, 1995;Mohr, Bowry, & Stocker, 1992) and phenolic components with superior antioxidant property (Lau et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation